SEGREGAÇÃO SOCIOESPACIAL, ECONOMIA URBANA E FOME: UMA ANALISE A PARTIR DA VILA OURO VERDE EM PONTA GROSSA-PR - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
The objective of this study is to analyze the relationship between socio-spatial segregation process, the consumption of food in the lower circuit of the urban economy, and food security. The proposed debate shows that the effects of a locational order in socio-spatially segregated environments bring the urban poor close to the food consumption at typical premises of the lower circuit. Such a fact is contributing to the worsening of quantitative and qualitative hunger. The spatial area of this analysis is the community of Vila Ouro Verde, located in Maria Otilia, in Ponta Grossa-PR. Result of an occupation during the year 2001, the community is the picture of spatial segregation and social exclusion. This research, in addition to showing a socioeconomic profile of families connected to the community, seeks to understand the factors that would help set up their habits of acquiring and consumption of food. We found that the higher prices, coupled with the low quality and little variety of existing products at small markets in the locality, collaborate for the formation of a food insecurity frame. Although the research presents a more exploratory nature, the results are relevant and provide a contribution to the study field of hunger
Keywords: espaço urbano; segregação socioespacial; economia urbana; segurança alimentar; urban space; socio segregation; urban economics; food security; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA